Liver gene therapy by lentiviral vectors reverses anti‐factor IX pre‐existing immunity in haemophilic mice. Issue 11 (16th September 2013) - Annoni, Andrea; Cantore, Alessio; Della Valle, Patrizia; Goudy, Kevin; Akbarpour, Mahzad; Russo, Fabio; Bartolaccini, Sara; D'Angelo, Armando; Roncarolo, Maria Grazia; Naldini, Luigi
<x xml:space="preserve">Abstract</x> A major complication of factor replacement therapy for haemophilia is the development of anti‐factor neutralizing antibodies (inhibitors). Here we show that liver gene therapy by lentiviral vectors (LVs) expressing factor IX (FIX) strongly reduces pre‐existing anti‐FIX antibodies and eradicates FIX inhibitors in haemophilia B mice. Concomitantly, plasma FIX levels and clotting activity rose to 50–100% of normal. The treatment was effective in 75% of treated mice. FIX‐specific plasma cells (PCs) and memory B cells were reduced, likely because of memory B‐cell depletion in response to constant exposure to high doses of FIX. Regulatory T cells displaying FIX‐specific suppressive capacity were induced in gene therapy treated mice and controlled FIX‐specific T helper cells. Gene therapy proved safer than a regimen mimicking immune tolerance induction (ITI) by repeated high‐dose FIX protein administration, which induced severe anaphylactoid reactions in inhibitors‐positive haemophilia B mice. Liver gene therapy can thus reverse pre‐existing immunity, induce active tolerance to FIX and establish sustained FIX activity at therapeutic levels. These data position gene therapy as an attractive treatment option for inhibitors‐positive haemophilic patients.